PROGRAM KARTU PRAKERJA SEBAGAI PROGRAM PEMBERDAYAAN DI BIDANG KETENAGAKERJAAN DI TENGAH PANDEMI - Septiyadi, Mochamad Rangga; Rahayu, Ety (Jurnal Pembangunan Manusia, 2022)
As predicted, Indonesia will experience a demographic bonus, starting in 2020 as indicated by the population of productive citizens group (15-64 years) which is larger than other population groups. In response to the situation, fundamental efforts need to be made to ensure that the demographic surplus can be an economic driver. In early 2020, the government launched the Pre-employment Card program. This program was launched in the midst of the Covid-19 pandemic which disrupted many aspects of society, especially the economy and health. This research examines the Pre-employment Card program from the point of view of the empowerment concept. Research is carried out by tracing government policies and regulations in carrying out this program. The results of the study found that the Pre-employment Card program seeks to implement empowerment goals as it seeks to build the strength of participants to engage in economic activities (work and entrepreneurship). The program develops 2 of 3 empowerment strategies by Jim Ife through policy and planning to provide fairer access to resources and opportunities to participate in community life as well as education and awareness raising to increase strength of the subject of empowerment.